Transformation Formulas of Lauricella's Function of the Fourth kind of Several Variables - Ahmed Ali Atash; Hussein Saleh Bellehaj (International Journal of Mathematics And its Applications, 2016)
The aim of this research paper is to derive transformation formulas for Lauricella's function of the fourth kind of several variables with the help of generalized Kummer's theorem on the sum of the series ${}_{2} F_{1} (-1)$ obtained by Lavoie et al. [10]. Some special cases of these formulas are also deduced.